New Hampshire. General Assembly order - New Hampshire. General Assembly
Order (1696 September 15), signed by John Usher, lieutenant governor, requiring that members of the general assembly swear allegiance to King William III, together with a reply (1696 September 16) from Nathaniel Fryar and Shadrach Watson listing members that had done so.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Previously cataloged as: Usher, John, 1648-1726. Letter, 1692.
Keywords: Fryar, Nathaniel; Usher, John, -- 1648-1726.; Watson, Shadrach; William -- III, -- King of England, -- 1650-1702.; Allegiance; Loyalty oaths; New Hampshire -- Politics and government -- To 1775.